(untitled) (KYAMC Journal, 2019)
Primary carcinoma of trachea also known as adenoid cystic carcinoma, adenocyst, malignant slyndroma. This tumor mostly occurs in the salivary gland (minor), lacrimal gland, trachea, paranasal sinuses and others. And also can occur in female reproductive tract, Bartholin gland and cervix. Carcinoma trachea is one of the very rare cases. Adenoid cystic carcinoma (ACC) of trachea is one of the very rare cases. This type of carcinoma is very slow growing cancer. Usually patients present with dyspnoea, asthma or bronchitis. After confirmed diagnosis 1st indication is surgery, if patient is not fit for surgery, can go to the laser ablation then Radio therapy. Our two cases of adenoid cystic carcinoma of trachea are, one is 30 years old female patient, her initial diagnosis was May, 2012 and another one 48 old male patient with history of smoking, his initial diagnosis was on July 2003. Both the patients are still alive. Now the female patient has bilateral pulmonary metastasis from September 2017. After treatment carcinoma of trachea can be metastasised to lung, brain, liver or others organs. Usually it happened after 12-15 years from initial diagnosis. However carcinoma of trachea has good prognosis if early diagnosed and treated. KYAMC Journal Vol. 10, No.-1, April 2019, Page 60-63